To study wear characteristics of cryogenically treated T42 high speed steel - Bandewar, Prof. Ashish; Mathapat, Prof. Nagesh; Kadam, Prof. Amol; Kazi, Prof. Juned (IJRDO - Journal of Applied Management Science, 2016)
The word, “cryogenics” is taken from two Greek words - “kryos” Which means cold or freezing, & “genes” meaning born or generated. Technologically, it means the study & use of materials (or other requirements) at very low temperatures. In general cryogenic treatment consists of slow cooling already heat treated parts to approximately -1960 C, holding at low temperature up to prescribed period, reheating without thermal shocks to room temperature & reheat to a moderately elevated temperature (150 to 3150 C) for about 1 or 2 hours, to “temper” the part for the stated purpose of reducing its brittleness. In this study cryogenic treatment is performed on AISI T42 HSS material & its wear characteristics are studied. Test of treated & untreated samples is taken on pin on disc wear testing machine at different load & RPM. The wear of the sample is measured. The wear resistance of the samples is also measured by weight loss method. The results are tabulated. An experimental effort to evaluate tool wear improvement by cryogenic treatment is the outcome of this study.